(untitled) (Bangladesh Journal of Medical Science, 2016)
Pancreatic fistula is an important and possible complication of left nephrectomy performed for inflammatory or malignant lesions of kidney. This may develop due to intimate relationship of tail of pancreas to left kidney. The objective is to report this unusual case of delayed pancreatic cutaneous fistula which patient developed eight years after left nephrectomy. The patient was managed conservatively with subcutaneous injections of octreotide which led to closure of fistula and healing of excoriation. Bangladesh Journal of Medical Science Vol.15(3) 2016 p.483-484